PEMANFAATAN DATA SATELIT DAN SISTIM INFORMASI GEOGRAFIS (SIG) UNTUK MENENTUKAN DAERAH PERIKANAN PANTAI DI LAUT SELATAN JAWA BARATPEMANFAATAN DATA SATELIT DAN SISTIM INFORMASI GEOGRAFIS (SIG) UNTUK MENENTUKAN DAERAH PERIKANAN PANTAI DI LAUT SELATAN JAWA BA - -, Hariyadi; Sudana, Ida Bagus (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Indonesia is maritime country surrounding by Wide Ocean. Two seasons that always happened in this area have been influence to the situation of oceanography and fisheries zone. The seasons which happened because influence by wind of monsoon, which are West Monsoon, East Monsoon, and the transition condition among both. The fishing ground information used Geography Information System (GIS) and remote sensing (RS) software and can be used for specific purpose. The most fundamental application is for dynamics population and distribution of fish in the ocean ecosystem. Environmental characteristics such as: temperature, thermo clines, salinity, ocean currents, and depth is identify potential fishing use technology of image satellite represent the way of identifying indirectly. From satellite data far identified by interconnected oceanography parameters sliver with fish habitation or potential schooling fish. Between oceanography parameter having relation with life of pelagic fish is water temperature go out to sea and fertility of territorial water area. Map of conducive satellite data, sea surface temperature ( SST) and content of chlorophyll-a the can be obtained by information about oceanography phenomena specially front thermal and upwelling representing potency area as fishing indicator. Fishing vessel usually leave fishing base without exactly knowing location of fishing ground so it always stay in uncertainty potential location of fishing ground, therefore its haul also becoming not surely. Meanwhile, in consequence of uncertainty fishing location, resulted fishing ship passing many time and fuel to looking for location of fishing ground. Successfully of the fishing operation is not depend by experience of fishing master but there are must be have the data where fishing ground located. And application of semi active fishing gear much help fisherman salary and require following by other sub-province especially at the west season, but having to limit by usage mesh size enabled by law or regulation so that small fish do not follow to be caught.
Keywords: Coastal Fisheries Zone, Remote Sensing, GIS, Monsoon, Fisheries Data, Satellite Data.